Quinolone Allergy - Edoabasi U. McGee; Essie Samuel; Bernadett Boronea; Nakoasha Dillard; Madison N. Milby; Susan J. Lewis (MDPI AG, 2019)
Quinolones are the second most common antibiotic class associated with drug-induced allergic reactions, but data on quinolone allergy are scarce. This review article discusses the available evidence on quinolone allergy, including prevalence, risk factors, diagnosis, clinical manifestations, cross-reactivity, and management of allergic reactions. Although the incidence of quinolone allergy is still lower than beta-lactams, it has been increasingly reported in recent decades, most likely from its expanded use and the introduction of moxifloxacin. Thorough patient history remains essential in the evaluation of quinolone allergy. Many diagnostic tools have been investigated, but skin tests can yield false-positive results and in vitro tests have not been validated. The drug provocation test is considered the test of choice to confirm a quinolone allergy but is not without risk. Evidence regarding cross-reactivity among the quinolones is limited and conflicting. Quinolone allergy can be manifested either as an immediate or delayed reaction, but is not uniform across the class, with moxifloxacin posing the highest risk of anaphylaxis. Quinolone should be discontinued when an allergic reaction occurs and avoided in future scenarios, but desensitization may be warranted if no alternatives are available.